Topical issues of guaranteeing cultural rights in the context of the implementation of the Association Agreement with the EU - Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Association Agreement with the EU in 2014 contains much more of the provisions for the implementation of cultural rights of citizens than the agreement on partnership and cooperation between the EU and Ukraine in 1994. This imposes great responsibilities for Ukraine in this sphere. Therefore, this article discusses the requirements for the legal regulation of culture, established in the EU and Ukraine’s obligations in this area deriving from these requirements.